(untitled) (Huellas, 2023)
The study of the distribution of species is increasingly necessary to understand the extinctions of megamammals that occurred during the late Pleistocene and early Holocene. Spatial analysis procedures, such as cartographic modeling and multicriteria evaluation techniques, allow finding spatial correspondences between geographic, environmental, faunal and human variables, to investigate the causes of these losses. From a conceptual approach, this paper analyzes the characteristics of the interdisciplinary approach between Geography and Paleontology, the role of spatial models in scientific realism, rationalist causality processes, and the possibilities of quantitative techniques in systemic spatial analysis, taking the case of the ground sloth Scelidotherium leptocephalum (Mylodontidae, Xenarthra). It concludes with a proposal for cartographic modeling as a logical construction of application in which the spatial dimension takes a central place of inquiry.